Hydrogen-induced nanohardness variations in a CoCrFeMnNi high-entropy alloy - Zhao, Yakai; Lee, Dong-Hyun; Lee, Jung-A; Kim, Woo-Jin; Han, Heung Nam; Ramamurty, Upadrasta; Suh, Jin-Yoo; Jang, Jae-il (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The influence of electrochemically charged hydrogen (H) on the hardness (H-N) of a CoCrFeMnNi high-entropy alloy (HEA) was investigated with nanoindentation. Upon charging, H-N of HEA increases by similar to 60%, which decreases gradually during subsequent aging at room temperature, and on prolonged aging, the alloy softens to an extent that H-N falls below that of the uncharged HEA. These H-induced mechanical property variations are rationalized in terms of the competition between solid solution hardening caused by H and excess vacancy creation due to deeply trapped H. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; STORAGE PROPERTIES; DISLOCATION NUCLEATION; NANOCRYSTALLINE; BEHAVIOR; NI; MICROSTRUCTURE; SUSCEPTIBILITY; DEFORMATION; STABILITY